Blast load assessment using hydrocodes - Luccioni, Bibiana Maria (2006)
The evaluation of pressures and impulses produced by blast loads with the aid of hydrocodes is studied in this paper. Numerical results are compared with those obtained with existing analytical expressions for different scaled distances and boundary conditions. In particular, the capacity of both methods to capture multiple reflections of the blast load is analyzed. The effects of mesh size on pressure and impulse distribution are also studied. Some interesting conclusions regarding the determination of the best mesh size for calculation of actual events are obtained. Finally, the analysis of blast load in the case of the AMIA (Israel–Argentina Mutual Association) building attack which occurred in Buenos Aires, Argentina in July 1994 is presented. A computational dynamic analysis was carried out over the congested urban environment that corresponds to the opposite rows of buildings of a block, in the same street. The results obtained for different positions of the explosive charge are presented and compared.